Non topological 1-soliton solution to resonant nonlinear schrodinger equation with kerr law nonlinearity - Subhaschandra Singh, Salam (International Journal of Physical Research, 2017)
In this paper, using the methods of ansatz, sine-cosine and He’s semi-inverse variation, non-topological 1-soliton solution to Resonant Nonlinear Schrodinger Equation with Kerr law nonlinearity is obtained. The results show that these methods are very effective ones for finding exact solutions to various types of nonlinear evolution equations appearing in the studies of science and engineering.